Change in momentum = \( \Delta \vec{P} \)

=\( \Delta P_{x}\hat{i} + \Delta P_{x}\hat{j} \)

Since\( \Delta P_{x} = 0 \) \(\Delta P_{y}\hat{j} = \vec{P}_{fy} – \vec{P}_{iy} \) \(P_{iy} = mvsin45 and P_{fy} = mvsin45 \)

=\( – 2mvsin45 = -\sqrt{2}mv_{j}\left | \Delta = \vec{P} \right | \)

=\( \sqrt{2}mv \)

Explore more such questions and answers at BYJU’S.

Was this answer helpful?

  
   

0 (0)

Upvote (0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question